Flocking and formation control for a group of nonholonomic wheeled mobile robots. Issue 1 (31st December 2023) - Pliego-Jiménez, Javier; Martínez-Clark, Rigoberto; Cruz-Hernández, César; Avilés-Velázquez, Jesús David; Flores-Resendiz, Juan Francisco
Abstract: The problem of flocking and formation of a group of nonholonomic wheeled mobile robot is addressed in this paper. Based on the cascade structure of the kinematic model, two kinematic controllers are proposed to achieve formation and flocking behaviors. The proposed control laws present a P and PI-like structure plus a feedforward term and do not require complex calculations. The interaction between the robots is modeled using graph theory. The performance of the proposed control laws is validated by experimental tests on a group of four differential-drive wheeled mobile robots.